Hypercomplementemia among Peridontal Disease Patients :Gengivitis (Global Journal of Medical Research, 2014)
Fifty gingivitis patients were diagnosis by dentist. The age range were 20 – 49 years. Blood and saliva samples were collected from the test patients and ten apparently Normal subjects as a control. Serum, whole and salivary proteins were subjected to C3 and C4 determinations. C3 and C4 concentration means of patients were higher than that for normal subject control. They approximate tow folds than that of control. Male approximate female patients levels of C3. Five combined C3 and C4 Hypercomplementemia out of 50 in both of the sexs. Six C4 and two C3 hyper complementemia were noted as single expression. Such hyper complementemia is of secondary type of infection and/ or inflammation responses of the gum.
Keywords: gingivitis; hypercomplementemia; saliva; serum; gum